Strategies and challenges to enhance the impact of e-service quality on institutional excellence: A proposed framework - Al Amin, Mohamed Sultan; Alsuwaidi, Salma Juma Jabr Juma (Scientific Research Publishing House (SRPH), 2023)
E-service quality plays a significant role to achieve success or failure in any organization, offering services online. It will increase the competition among the organizations, to attract the customers on the basis of the quality of service provided by the organization. Better e-service quality will enhance the relationship with customers and their satisfaction. So, the measurement of eservice quality is very important, but it is a complex process due to the complex nature of services. Literature predicts that there is a lack of universal definition of e-service quality. Hence, the main objective of implementing an E-service quality is to improve the organizations business processes and operations for improved business institutional excellence. But not all organizations have been successful in the E-service quality. The aim of this paper was an attempt to enhance the Impact of E-service quality on institutional excellence as a part of corporate strategy in an organization. The results confirmed the positive and significant effects of E-service quality to enhance institutional excellence .The moderator role of company quality policy between E-service quality and institutional excellence also was confirmed. Throughout this study, further details and valuable implications have been discussed. Findings also help practitioners and managers make proper decisions when implementing E-service quality and excellence practices in their organizations. With the joint effect of E-service quality and institutional excellence, organizations can achieve maximum strong excellence and remain in a competitive market, which may assist to maintain and improve the performance and effectiveness of e-service quality to retain customers.